Ultrafast charge transfer dynamics pathways in two-dimensional MoS2-graphene heterostructures: A core-hole clock approach - Garcia-Basabe, Yunier; Rocha, Alexandre R. [UNESP]; Vicentin, Flávio C.; Villegas, Cesar E. P. [UNESP]; Nascimento, Regiane; Romani, Eric C.; De Oliveira, Emerson C.; Fechine, Guilhermino J. M.; Li, Shisheng; Eda, Goki; Larrude, Dunieskys G. (Royal Society of Chemistry (RSC), 2017)
Two-dimensional van der Waals heterostructures are attractive candidates for optoelectronic nanodevice applications. The charge transport process in these systems has been extensively investigated, however the effect of coupling between specific electronic states on the charge transfer process is not completely established yet. Here, interfacial charge transfer (CT) in the MoS2/graphene/SiO2 heterostructure is investigated from static and dynamic points of view. Static CT in the MoS2-graphene interface was elucidated by an intensity quenching, broadening and a blueshift of the photoluminescence peaks. Atomic and electronic state-specific CT dynamics on a femtosecond timescale are characterized using a core-hole clock approach and using the S1s core-hole lifetime as an internal clock. We demonstrate that the femtosecond electron transfer pathway in the MoS2/SiO2 heterostructure is mainly due to the electronic coupling between S3p-Mo4d states forming the Mo-S covalent bond in the MoS2 layer. For the MoS2/graphene/SiO2 heterostructure, we identify, with the support of density functional calculations, new pathways that arise due to the high density of empty electronic states of the graphene conduction band. The latter makes the transfer process time in the MoS2/graphene/SiO2/Si twice as fast as in the MoS2/SiO2/Si sample. Our results show that ultrafast electron delocalization pathways in van der Waals heterostructures are dependent on the electronic properties of each involved 2D material, creating opportunities to modulate their transport properties.